2017
DOI: 10.1016/j.tibs.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Stressed and Inflamed, Can GSK3 Be Blamed?

Abstract: Psychological stress has a pervasive influence on our lives. In many cases adapting to stress strengthens organisms, but chronic or severe stress is usually harmful. One surprising outcome of psychological stress is activation of an inflammatory response, resembling inflammation caused by infection or trauma. Excessive psychological stress and the consequential inflammation in the brain can increase susceptibility to psychiatric diseases, such as depression, and impair learning and memory, including in some pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 71 publications
(95 reference statements)
5
104
0
Order By: Relevance
“…To explore the potential signaling regulation of rFGF21, we then examined the Akt/GSK-3β pathway alteration. It has been known that Akt deactivation and GSK-3β activation play dominant roles in promoting neuroinflammation [69, 70]. We found that Akt was deactivated by reducing its phosphorylation, while GSK- 3β was activated by decreasing its phosphorylation in hippocampal tissues of HFD mice; however, rFGF21 treatment rescued Akt deactivation and reversed GSK-3β activation status (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…To explore the potential signaling regulation of rFGF21, we then examined the Akt/GSK-3β pathway alteration. It has been known that Akt deactivation and GSK-3β activation play dominant roles in promoting neuroinflammation [69, 70]. We found that Akt was deactivated by reducing its phosphorylation, while GSK- 3β was activated by decreasing its phosphorylation in hippocampal tissues of HFD mice; however, rFGF21 treatment rescued Akt deactivation and reversed GSK-3β activation status (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…GSK3 acts a potent driver of inflammation, rendering GSK3 inhibitors a promising target of anti-inflammatory research [17,121]. It is well established that enzymatically active GSK3 acts as a crucial positive regulator of pro-inflammatory cytokines (e.g., TNF, interleukin (IL-)1β, IL-6 [15], IL-17, IL-18 [122], IL-23 [94], IL-12, IFN-γ [17]), chemokines (IL-8 [122], C-C motif chemokine ligand (CCL) 2 [17], 3, 4 [123], and 12, C-X-C motif chemokine ligand (CXCL) 1, 2, 5 [17], and 10 [124]), and further pro-inflammatory mediators (e.g., nitric oxide (NO) [125] or prostaglandin E2 [126]). Vice versa, anti-inflammatory cytokines, such as IL-2 [127], IL-10 [90], IL-22 [128], IL-33 [129], and IL-1 receptor antagonist [130], are negatively regulated by GSK3.…”
Section: Cytokine Expressionmentioning
confidence: 99%
“…In an alternative GSK3α KO model, mice were also viable but characterized by higher body weight, heavier organs (especially brain, heart, and testis), male infertility, and slightly reduced lifespan [136]. Interestingly, despite a multitude of indications that GSK3 has an essential influence on inflammatory processes [17,121], GSK3α KO organisms are not characterized by significant signs of altered immune reactions, implying that GSK3β may be the more prominent paralog with respect to immune regulation.…”
Section: Gsk3 Ko Modelsmentioning
confidence: 99%
See 2 more Smart Citations